Efficacy and safety of Gushen Antai Pills combined with dydrogesterone in the treatment of threatened miscarriage: a systematic review and meta-analysis - Chen, Kai; Liu, Xiaoxia; Meng, Xianhua; Li, Hui; Yang, Chenchen; Wang, Xiaohong (Frontiers in Pharmacology, 2023)
Background: Despite some progress has been made in the pathogenesis and treatment of threatened miscarriage (TM), conventional treatment remains suboptimal. Thus, complementary medicine gradually become a new treatment option for treating TM. Gushen Antai Pills (GAP), a classic prescription of Traditional Chinese medicine (TCM), has became a popular complementary therapy to conventional western medicine (dydrogesterone) in treating TM in recent years. However, a systematic summary and analysis for its therapeutic effects is lacking. This meta-analysis aimed to systematically evaluate the effectiveness and safety of GAP combined with dydrogesterone in the treatment of TM. Methods: A systematic search across seven electronic databases was conducted from inception to September 17, 2022. Studies were included if they were randomized controlled trials (RCTs) evaluating the effect of integrating GAP and dydrogesterone in patients with TM, and reported the outcomes of interest. All statistical analyses were conducted using the Revman5.3 and Stata 13 software. The GRADE system was used to evaluate the quality of evidence. Results: Ten eligible RCTs involving 950 participants were contained in this meta-analysis. The pooled analysis showed that GAP combined with dydrogesterone can significantly reduce the incidence of early pregnancy loss (RR: 0.29; 95%CI: 0.19–0.42; P<0.00001) and alleviate clinical symptoms (RR: 1.39; 95%CI: 1.22–1.59; P<0.00001), compared with treatment of dydrogesterone alone. Also, meta-analysis indicated that integrating GAP and dydrogesterone is more effective than using dydrogesterone alone in improving hormone levels (serum levels of progesterone, β-HCG and estradiol) for women with TM (all P<0.00001). Meanwhile, the combined effects with significant heterogeneity also showed favorable consistency in the sensitivity analyses, indicating a good stability of present results. Moreover, no significant differences between GAP combined with dydrogesterone and control group on adverse events was identified. The overall GRADE qualities were low to moderate. Conclusions: The overall available evidence suggested that GAP combined with dydrogesterone had significant effects in improving pregnancy success rate, clinical symptoms and hormone levels for women with TM, with considerable safety and reliability. However, due to the partial heterogeneity, suboptimal quality and high risk of bias of some included studies, further rigorously designed RCTs are required.